2008
DOI: 10.1149/1.2816226
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydrogen on Corrosion of Tb[sub 0.3]Dy[sub 0.7]Fe[sub 1.92]

Abstract: The effect of hydrogen on the corrosion behavior of rare-earth-based magnetostrictive material Tb0.3Dy0.7Fe1.92 was studied after cathodic charging of hydrogen. The aqueous solutions used for understanding electrochemical behavior were 3.5% NaCl and 0.01 N Na2SO4 , in freely aerated and deaerated conditions. The severity of hydrogen attack in the presence of chloride ions increased with increasing hydrogen charging duration. Terraced and cleavagelike faceted features were evident on the surfaces after hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…The destabilisation of surface film in the presence of Cl 2 resulted in hydrogen embrittlement of material. 24 The present study showed improved corrosion behaviour in alkaline solutions, due to the formation of protective surface passive film. Therefore, encapsulating the material in chloride free alkaline environment can be advantageously explored as a method of protection for this material.…”
Section: Electrochemical Impedance Spectroscopysupporting
confidence: 59%
See 3 more Smart Citations
“…The destabilisation of surface film in the presence of Cl 2 resulted in hydrogen embrittlement of material. 24 The present study showed improved corrosion behaviour in alkaline solutions, due to the formation of protective surface passive film. Therefore, encapsulating the material in chloride free alkaline environment can be advantageously explored as a method of protection for this material.…”
Section: Electrochemical Impedance Spectroscopysupporting
confidence: 59%
“…32 Therefore, it is more likely at higher potentials of polarisation scan. Thus, it can be anticipated that Previous studies on corrosion behaviour of Tb 0?3 Dy 0?7 Fe 1?92 23,24 revealed its active nature in near neutral aqueous solutions with and without the presence of Cl 2 . Corrosion rates were higher in the former condition, particularly in the absence of oxygen.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 95%
See 2 more Smart Citations
“…Detailed studies on several aspects of corrosion of commercial-grade Tb 0.3 Dy 0.7 Fe 1.92 ͑commercially called Terfenol-D͒ have recently been concluded. [1][2][3][4][5] Corrosion of these ͑Tb,Dy͒Fe 2 -based magnetostrictive materials is of scientific, commercial, and strategic concerns, as this material is the nextgeneration material for active sonar applications. Apart from this, Terfenol-D finds varied applications, such as in tools for well cleaning in the petroleum, oil, and gas industries, in fuel injection, and in medical appliances.…”
mentioning
confidence: 99%